Pengaruh Senam Bugar Muhammadiyah terhadap Kebugaran Jasmani pada Siswa Usia 16-19 Tahun di Sekolah SMK Nurul Fajar Kabupaten Bogor Tahun Pelajaran 2019/2020 - marselianda, riska (utile: Jurnal Kependidikan, 2021)
This research aimed to determine the effect of physical fitness though Muhammadiyah gymnastics on nursing student of SMK Nurul Fajar, Bogor district, 2019/2020 academic year in the form of quantitative research with experimental methods and sampling was carried out using purposive sampling technique, amounting, to 4 people from 22 populations. This research was conducted by measuring physical fitness through TKJI before and after being given Muhammadiyah fitness treatment. This research method uses the normality test with pretest results known as asymp.sig = 0.995 with normal information and posttest results known asymp.sig = 0.846 and information, normal, from the T test results with the calculation obtained 0.495. This result is greater than 0.05, this result indicates that the hypothesis Ha is rejected, which means that Ho = there is no significant effect of Muhammadiyah fitness training Homogeneity test using SPSS 21, the results of the study using muhammmadiyah fitness exercises have an effect which is in the "moderate" category but not significant in class XII nursing students of SMK Nurul Fajar, Bogor Regency.